Field assessment of a novel sensor for measuring noncondensable gases in steam sterilizers - Francesco Tessarolo; Michela Masè (Scientific Reports)
Abstract Steam sterilization is widely used to process heat-resistant instruments in hospital settings. The presence of non-condensing gases (NCGs) in the steam may severely impact heat transfer and process efficacy. However, the current practice does not include routine NCG monitoring in the sterilizer chamber. This study evaluates the capability of a novel sensor to detect and quantify NCGs in the sterilizer chamber under different conditions occurring in the field. A commercially available steam sterilizer was equipped with the NCG sensor, and a range of sterilization processes were run. NCGs in the sterilizer chamber were obtained by inadequate vacuum during conditioning, or by introducing controlled air volumes during the conditioning or the exposure phase using different access points. Tests were performed with or without load into the chamber. NCG measurements were analysed by mixed-effects models. The sensor provided reproducible measurements of NCGs resulting from ineffective conditioning (marginal R2 = 0.88) or introduced during the conditioning (marginal R2 = 0.97) and exposure phase (marginal R2 = 0.96), with negligible effects of access points or load amounts. The availability of a quantitative measure of steam composition, added to time and temperature, represents a relevant advancement in real-time monitoring of every sterilization process, toward the full-parametric release of steam sterilized loads.